2008
DOI: 10.1051/agro:2008032
|View full text |Cite
|
Sign up to set email alerts
|

Pollution maps of grass contamination by platinum group elements and polycyclic aromatic hydrocarbons from road traffic

Abstract: -The increase in deposition of air pollutants such as the platinum group elements (PGEs) Pt, Pd and Rh, and polycyclic aromatic hydrocarbons (PAHs) from vehicles on plants has raised concerns about the risk for the quality of food and, in turn, for human health. Here, we report the first pollution maps of PGEs and PAHs at the agricultural scale. PGEs have recently emerged in ecosystems due to their massive use as catalysts in the automobile industry. PAHs are combustion by-products known for their carcinogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Dan-Badjo et al (2007) placed ryegrass (Lolium perenne) pots in the vicinity of a highway and found that the high molecular weight PAHs (5 and 6 rings) represented almost 23% of the total PAH concentrations. In a following study, however, spatial distribution of accumulation was depicted (Dan-Badjo et al 2008). It was recorded that concentration of accumulated PAHs was the highest between 0 and 10 m on both sides of the road than it started to decrease rapidly.…”
Section: Source Appointmentmentioning
confidence: 92%
“…Dan-Badjo et al (2007) placed ryegrass (Lolium perenne) pots in the vicinity of a highway and found that the high molecular weight PAHs (5 and 6 rings) represented almost 23% of the total PAH concentrations. In a following study, however, spatial distribution of accumulation was depicted (Dan-Badjo et al 2008). It was recorded that concentration of accumulated PAHs was the highest between 0 and 10 m on both sides of the road than it started to decrease rapidly.…”
Section: Source Appointmentmentioning
confidence: 92%